Diallyl disulphide-loaded spherical gold nanoparticles and acorn-like silver nanoparticles synthesised using onion extract: catalytic activity and cytotoxicity - You Jeong Lee; Song-Hyun Cha; Hyunjo Kim; Sung Eun Choi; Seonho Cho; Youmie Park (Artificial Cells, Nanomedicine, and Biotechnology)
Onion (Allium cepa) extract was used for the green synthesis of gold and silver nanoparticles. Each colloidal solution exhibited surface plasmon resonance, with a peak at 532 nm for gold nanoparticles and 391 nm for silver nanoparticles. Microscopic results confirmed the presence of spherical shapes. The X-ray diffraction pattern demonstrated a face-centered cubic structure. Both nanoparticles had negative zeta potentials and retained colloidal stability in cell culture medium. Catalytic applications were evaluated for 4-nitrophenol reduction and methyl orange degradation reactions by monitoring with UV-visible spectrophotometry. Furthermore, the nanoparticles demonstrated no significant cytotoxicity against human pancreas ductal adenocarcinoma cells (PANC-1) and human colorectal adenocarcinoma cells (HT-29). PEGylation and diallyl disulphide loading of the gold and silver nanoparticles meaningfully reduced the cell viability of both cell lines. Furthermore, diallyl disulphide loading resulted in more cytotoxicity against PANC-1 cells than against HT-29 cells. Additionally, the gold nanoparticles were more cytotoxic than the silver nanoparticles upon diallyl disulphide loading. Interestingly, after PEGylation and diallyl disulphide loading, the silver nanoparticles exhibited acorn-like shapes, while the gold nanoparticles retained spherical shapes. This result suggested that nanoparticles green-synthesised by onion extract have possibilities as nanocatalysts and drug delivery nanocarriers for catalytic and nanomedicine applications.